Oscillations and waves of intracellular CA2+ in cardiac-muscle-cells - Orchard, Clive H.; Mustafa, Mohd Rais; White, Edward (Elsevier, 1995)
When cardiac muscle cells become overloaded with Ca2+, spontaneous releases of Ca2+ from the sarcoplasmic reticulum can occur. Such spontaneous releases normally originate within a localized region of the cell and propagate as a wave throughout the cell. The amplitude and frequency of these Ca2+ releases increase with the degree of Ca2+ loading of the cell, and are abolished by interventions which inhibit sarcoplasmic reticulum function. It is still not clear whether these releases are triggered by a rise in the Ca2+ in the lumen of the sarcoplasmic reticulum or by a rise in cytoplasmic Ca2+. Such releases may, however, by activating inward currents, depolarize the cell membrane and thus be arrhythmogenic; they may also, by decreasing the amount of Ca2+ within the sarcoplasmic reticulum, decrease the strength of a stimulated contraction.